Morphometric and Meristic Characterization of Hairtails Trichiurus lepturus Linnaeus, 1758 (Scombriformes: Trichiuridae) from the Northern Coast of Java, Indonesia - Adhimas Febri Aryantojati; Murwatoko Murwantoko; Eko Setyobudi (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchThe most significant morphological variation was the snout length and caudal peduncleT. lepturus from the coast of Pati and Cirebon have a high morphometric character resemblance and possibly are members of the same populationT. lepturus in Demak waters formed a separate population group from T. lepturus from the coast of Pati and Cirebon, however still in the same species AbstractHairtails (Trichiurus spp.) are economically important fisheries resources and have become an export commodity. In Indonesia, there are several hairtail species; however, each species distribution is not yet certainly known. This study aimed to identify and determine the morphometric and meristic character of the hairtail from the northern coast of Java, Indonesia. Fish specimens were obtained from fishermen catches in the north coast of Pati and Demak (Central Java) and the northern coast Cirebon (West Java), which captures the fish in less than one-week fishing operation. Fish samples were grouped based on morphological similarities identified in previously published works. After that, 22 morphometric and four meristic characters were measured and counted. Principal Component Analysis and Discriminant Analysis were used to analyze morphometric data, while the meristic data were compared to the available published works. The hairtail caught at the northern coast of Java was long, flat, silvery in color, and had a sagittal crest, with the fin formula being D.III.125-134, P.I.10, and A.I.98-104. According to the morphological and meristic characters, the hairtail caught at Java's northern coast was identified as Trichiurus lepturus. The most significant morphological variation was the snout length and caudal peduncle. The PCA and scattergram analyses showed that T. lepturus from the coast of Pati and Cirebon have a high morphometric character resemblance and possibly are members of the same population.  T. lepturus in Demak waters formed a separate population group from T. lepturus from the coast of Pati and Cirebon, however still in the same species.